PELATIHAN DAN PENDAMPINGAN PENGGUNAAN APLIKASI QUIZIZZ SEBAGAI MEDIA PEMBELAJARAN - Irnawati; I Wayan Arsana; A Qomaru Zaman; Melania Tesa Iana Maya Anugraheni; Jihan Aulia Salma (Kanigara, 2022)
The purpose of writing this article is to provide an understanding of the use of the quizizz application through training and assistance in the use of the quizizz application as a learning medium at the Muhammadiyah 1 Taman High School, Sidoarjo Regency, East Java Province. This training activity is a form of training and mentoring to increase awareness of the importance of understanding the use of digital and technology platforms. Implementation methods with workshops such as presentation models, lectures, discussions, and counseling. The results of the study provide an answer that the quality of student understanding lies in the creativity of the teacher in the use of interesting digital platforms such as the quizizz application. So, providing training and assistance related to the use of the quizizz application is important, especially for teachers and especially for high schools for students who are enthusiastic about learning.